ISLAMIC STOCK MARKET PERFORMANCE PRE-COVID-19: EMPIRICAL EVIDENCE FROM JAKARTA ISLAMIC INDEX - Supriani, Indri; Herianingrum, Sri; Ninglasari, Sri Yayu; Budi, Ryan Setya (Universitas Airlangga, 2022)
Islamic stock market has experienced massive growth globally, including in Indonesia. This study aims to investigate the predicting factors of the Indonesian Islamic stock market that presents by the stock price of the Jakarta Islamic Index (JII). Adopted the Augmented Distributed Lag (ARDL) approach, this study uses monthly data from January 2007 to February 2020. This study uses five macroeconomic variables, namely consumer price index, exchange rate, crude oil price, world gold price, and Dow Jones Islamic Index (DJIM), to determine the JII's stock price. As a result, the JII's price volatility is significantly driven by the macroeconomic variables simultaneously. Importantly, this study reports that world gold price and DJIM return to become the most crucial factors influencing the ' 'JII's stock price volatility in short and long-run investment periods. This study has passed robustness checks by conducting three out of sample periods, namely 25%, 50%, and 75% out of sample. The 75% and 50% out of sample data revealed an identical result. Thus, this study suggests that the investor evaluates the crude oil price and world gold price fluctuation to predict the price of JII. This study offers practical implications for policymakers and practitioners and recommendations for future research.